Anaplastic Thyroid Cancer: The Addition of Systemic Chemotherapy to Radiotherapy Led to an Observed Improvement in Survival—A Single Centre Experience and Review of the Literature - Natalie M. Lowe; Sean Loughran; Nicholas J. Slevin; Beng K. Yap (The Scientific World Journal)
Introduction. Anaplastic thyroid carcinoma (ATC) is rare yet accounts for up to 50% of all thyroid cancer deaths. This study reviews outcomes of patients with confirmed ATC referred to a tertiary oncology centre plus reviews the literature to explore how poor outcomes may be improved. Materials and Methods. The management and outcomes of 20 patients with ATC were reviewed. Results. Median age at diagnosis was 69.5 years. 19 patients died due to ATC, 40% of whom died from asphyxiation. Median survival for all cases was 59 days. Patients who had previous surgery prior to other treatment modalities had a longer median survival overall compared to those who had not had previous surgery (142 days compared to 59 days) and produced the one long-term survivor. Chemotherapy followed by radiotherapy (without previous surgery) was associated with longer median survival (220 days). Palliative radiotherapy alone did not decrease the rate of death by asphyxiation when compared to other single modality treatments. Conclusion. Multimodality treatment including surgery when feasible remains the best strategy to improve survival and prevent death from asphyxiation in the management of ATC. The addition of chemotherapy to our institutional protocol led to improved survival but prognosis remains very poor.